Value relevance of accounting numbers: Malaysian high-tech companies - Md Daud, Seri Ayu Masuri; Othman, Intan Waheedah; Ghazali, Aziatul Waznah (2011)
Using sample of companies listed in MESDAQ, this paper investigates whether the anomalous relationship between negative earnings and stock prices for the high-tech companies exists in Malaysia. We found evidence rejecting this anomalous relationship and hence failed to accept the claim that including book value in the valuation specification eliminates the anomalous relationship. Surprisingly, test results also indicate that sales are not value relevant in the valuation of high-tech loss making firms in Malaysia.